Evaluation and management of pediatric patients with recurrent follicular tonsillitis - Hala Mohammed Hussein; Aya Mohammed Fattouh; Faten Mohamed Abdelaziz; Reem Ibrahim Ismail (Cairo : Hala Mohammed Hussein, 2012)
Pharyngitis due to group (A) beta hemolytic streptococcus (GABHS) assumes a special significance because of the risk of subsequent theumatic fever (RF) and chronic rheumatic heart disease (RHD) in the infected child. About 10-30% of acute pharyngitis is caused by (GABHS). About 0.3-3% of patients of untreated (GABHS) pharyngitis go on to develop RF
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Pediatrics
Issued also as CD
Keywords: Fotheular tonsillito; Pediatrics; Pharyngitis